A Novel von Hippel Lindau Gene Intronic Variant and Its Reclassification from VUS to Pathogenic: the Impact on a Large Family. Issue 6 (2nd September 2015) - Sexton, A.; Rawlings, L.; McKavanagh, G.; Simons, K.; Winship, I.
Abstract: We present a case where a variant of uncertain significance in the von Hippel Lindau syndrome gene ( VHL ) was identified in a proband with haemangioblastoma, and in a second degree relative with phaeochromocytoma. Initial uncertainty due to the unclear nature of the variant created psychosocial challenges for this family, in which four other genetic conditions were also present. Subsequent RNA studies confirmed this as a novel pathogenic mutation affecting splicing of exon 2. A third relative has since been diagnosed with haemangioblastoma. We suggest that this mutation possibly has reduced penetrance as there was no history of haemangioblastoma, renal tumours (apart from small cysts) or other VHL tumours among five mutation positive and seven untested adult relatives at 50 % risk of the VHL mutation (average age 46 years, range 18–70 years). This case presents a novel VHL splicing mutation and highlights the psychosocial and medical value of additional laboratory studies on uncertain variants for individuals, their families and for the health professionals providing advice and counseling.